An electret film-based triboelectric nanogenerator with largely improved performance via a tape-peeling charging method. (June 2018) - Zhang, Hanlu; Feng, Shan; He, Delong; Xu, Yiguo; Yang, Minhao; Bai, Jinbo
Abstract: Harvesting energy from the environment is a sustainable solution for powering decentralized sensor networks, Internet of Things systems, etc. In this work, a triboelectric nanogenerator (TENG) based on the fluorinated ethylene propylene (FEP) electret film is investigated to generate electricity from mechanical motions in the environment, and its working principle is explained with a variable capacitance model. For the first time, the validity of this model is verified with a capacitor discharge curve fitting method. Based on this model, the maximum output energy of the TENG per working cycle is calculated, which could be useful for comparing the property of TENGs working under different environmental conditions. An adhesive tape-peeling process is innovatively used to charge the FEP electret film, which is facile and effective for increasing the charge amount on the film without using any complex equipment. Through this method, the surface potential of a 4 cm × 4 cm FEP film is improved from −360 V to −2850 V, the output negative voltage peak of the same-sized TENG is improved from −83 V to −363 V, and for a wind-driven 8 cm × 8 cm sized TENG, its average output power to charge a 10μF capacitor is improved from 2.5 μW to 19.8 μW. The ability of this TENG in generating electricity from low-frequency human motions to directly light up light emitting diodes (LEDs) is also demonstrated. Graphical abstract: A variable capacitance model for the FEP electret film-based TENG is explained and experimentally verified, and a tape-peeling process is innovatively used to charge the electret to greatly improve the performance of the TENG. fx1 Highlights: An FEP electret film-based triboelectric nanogenerator is investigated in detail. A variable capacitance model for the TENG is proposed and experimentally verified. A facile tape-peeling process is innovatively used to charge the electret film.